Estimativas dos parâmetros genéticos para seleção de árvores de Eucalyptus - De Moraes, Cristiano Bueno [UNESP]; Brizolla, Thiago Fernandes [UNESP]; Teixeira, Lorena Gama; Zimback, Léo; Tambarussi, Evandro Vagner; Chaves, Raul; De Moraes, Mário Luiz Teixeira [UNESP]; Mori, Edson Seizo [UNESP] (My University, 2014)
Eucalyptus grandis is the most commonly cultivated species in commercial stands in Brazil and throughout the world. The species is planted as a cultivar, by seed, e also by clonal plantings of its interspecific hybrids. The study have as objective to analyze the correlations between juvenile and at the end of rotation, aiming to get support for procedures of early selection in forest tree breeding programs. The experiments were set up in two trials in two localities: Angatuba and Lençois Paulista, both in São Paulo State, Brazil. The experimental design was randomized blocks, with 10 replications, six plants per plot, 3 x 2 spacing and 76 progenies. The diameter at breast height, plant height, and wood volume were the studied traits. The evaluations were made through the consecutive years (2, 3, 4, and 5 of age) in Lençois Paulista (Locality 2), and in Angatuba (Locality 1) where annual evaluations from de second to the sixth years of age were done. The results have shown that early selection for wood volume can be done by the 2 years of age, with 0.83 of genetic correlation with the age of final rotation (6 years), and it reaches the value of 0.93, between 3 and 6 years of age, meaning that at half rotation, almost all the selection can be done for the final of rotation.
Estimates of genetic parameters for selection of trees in Eucalyptus
Keywords: Correlation; Improvement; Plants selection